In vivo measurement of an Apelin gradient with a genetically encoded APLNR conformation biosensor - Lukas Herdt; Hannes Schihada; Michael Kurz; Sebastian Ernst; Jean Eberlein; Peter Kolb; Cornelius Krasel; Moritz Bünemann; Christian S. M. Helker (Nature Communications)
Abstract The Apelin receptor (APLNR), a class A G-protein coupled receptor, plays a crucial role during cardiovascular development and tumor angiogenesis. To understand its spatiotemporal activity in health and disease is fundamental for the development of drugs to manipulate its activation state. To obtain this understanding, here we develop a tool box of various APLNR conformation biosensors, based on FRET, BRET and the conformation-sensitive fluorophore circularly permuted GFP (cpGFP), with further focus on its in vivo application. We demonstrate the functionality of our biosensors by pharmacological characterization and signal transduction analysis in vitro. Two APLNR-cpGFP biosensors show superior signal-to-noise ratio and are further analyzed for their in vivo applicability. In zebrafish embryos, APLNR-cpGFP biosensors are able to bind both endogenous ligands, Apelin and Apela, and visualize endogenous Aplnr activity in growing blood vessels. Moreover, we are able to measure an Apelin ligand gradient across cellular distances in vivo. Hence, these APLNR conformation biosensors are powerful tools to resolve the spatiotemporal Apelin signaling activity in health and disease.